Adaptation can help mitigation: an integrated approach to post-2012 climate policy. (29th April 2013) - Bosello, Francesco; Carraro, Carlo; De Cian, Enrica
Abstract: This paper analyzes the optimal mix of adaptation and mitigation expenditures in a cost-effective setting, in which countries cooperate to achieve a long-term stabilization target (550 CO2 -eq). It uses an Integrated Assessment Model (AD-WITCH) that describes the relationships between different adaptation modes (reactive and anticipatory), mitigation and capacity building to analyze the optimal portfolio of adaptation measures. Results show that the optimal intertemporal distribution of climate policy measures is characterized by early investments in mitigation followed by large adaptation expenditures a few decades later. Hence, the possibility of adapting does not justify postponing mitigation. Moreover, a climate change policy combining mitigation and adaptation is less costly than mitigation alone. In this sense mitigation and adaptation are shown to be strategic complements rather than mutually exclusive.